Multiphasic Regulation of Systemic and Peripheral Organ Metabolic Responses to Cardiac Hypertrophy. (April 2017) - Liew, Chong Wee; Xu, Shanshan; Wang, Xuerong; McCann, Maximilian; Whang Kong, Hyerim; Carley, Andrew C.; Pang, Jingbo; Fantuzzi, Giamila; O'Donnell, J. Michael; Lewandowski, E. Douglas
Abstract : Background—: Reduced fat oxidation in hypertrophied hearts coincides with a shift of carnitine palmitoyl transferase I from muscle to increased liver isoforms. Acutely increased carnitine palmitoyl transferase I in normal rodent hearts has been shown to recapitulate the reduced fat oxidation and elevated atrial natriuretic peptide message of cardiac hypertrophy. Methods and Results—: Because of the potential for reduced fat oxidation to affect cardiac atrial natriuretic peptide, and thus, induce adipose lipolysis, we studied peripheral and systemic metabolism in male C57BL/6 mice model of transverse aortic constriction in which left ventricular hypertrophy occurred by 2 weeks without functional decline until 16 weeks (ejection fraction, −45.6%; fractional shortening, −22.6%). We report the first evidence for initially improved glucose tolerance and insulin sensitivity in response to 2 weeks transverse aortic constriction versus sham, linked to enhanced insulin signaling in liver and visceral adipose tissue (epididymal white adipose tissue [WAT]), reduced WAT inflammation, elevated adiponectin, mulitilocular subcutaneous adipose tissue (inguinal WAT) with upregulated oxidative/thermogenic gene expression, and downregulated lipolysis and lipogenesis genes in epididymal WAT. By 6 weeks transverse aortic constriction, the metabolic profile reversed with impaired insulin sensitivity and glucose tolerance, reduced insulin signaling in liver, epididymal WAT and heart, and downregulation of oxidative enzymes in brown adipose tissue and oxidative and lipogenic genes in inguinal WAT. Conclusions—: Changes in insulin signaling, circulating natriuretic peptides and adipokines, and varied expression of adipose genes associated with altered insulin response/glucose handling and thermogenesis occurred prior to any functional decline in transverse aortic constriction hearts. The findings demonstrate multiphasic responses in extracardiac metabolism to pathogenic cardiac stress, with early iWAT browning providing potential metabolic benefits. Abstract : Supplemental Digital Content is available in the text.